Open Source 3D Multipurpose Measurement System with Submillimetre Fidelity and First Application in Magnetic Resonance. Issue 1 (December 2017) - Han, Haopeng; Moritz, Raphael; Oberacker, Eva; Waiczies, Helmar; Niendorf, Thoralf; Winter, Lukas
Abstract Magnetic resonance imaging (MRI) is the mainstay of diagnostic imaging, a versatile instrument for clinical science and the subject of intense research interest. Advancing clinical science, research and technology of MRI requires high fidelity measurements in quantity, location and time of the given physical property. To meet this goal a broad spectrum of commercial measurement systems has been made available. These instruments frequently share in common that they are costly and typically employ closed proprietary hardware and software. This shortcoming makes any adjustment for a specified application difficult if not prohibitive. Recognizing this limitation this work presentsCOSI Measure, an automated open source measurement system that provides submillimetre resolution, robust configuration and a large working volume to support a versatile range of applications. The submillimetre fidelity and reproducibility/backlash performance were evaluated experimentally. Magnetic field mapping of a single ring Halbach magnet, a 3.0 T and a 7.0 T MR scanner as well as temperature mapping of a radio frequency coil were successfully conducted. Due to its open source nature and versatile construction, the system can be easily modified for other applications. In a resource limited research setting, COSI Measure makes efficient use of laboratory space, financial resources and collaborative efforts.